Indolent adult T‐cell leukaemia‐lymphoma successfully treated with bexarotene in an eldery patient - Maho Nakashima; Motoi Takenaka; Hiroyuki Murota (Wiley, 2023)
Abstract Adult T‐cell leukaemia‐lymphoma (ATL) is a mature T‐cell malignancy, with more than 50% of cases showing cutaneous involvement. Patients with cutaneous‐type ATL (cATL) in the indolent type (i.e., favourable chronic or smouldering type) can usually be managed by watchful waiting and they are primarily treated with skin‐directed therapies until the disease progresses to acute crisis, with multiple tumours usually considered intractable. ATL tends to present in older patients, and those with multiple cATL tumours face difficulties in obtaining multiagent chemotherapy used for aggressive types. Although bexarotene is a third‐generation novel retinoid X receptor‐selective retinoid treatment that is effective for cutaneous T‐cell lymphoma, few reports have demonstrated its effectiveness for cATL. We describe an 86‐year‐old woman with cATL treated safely and successfully with a combination of oral bexarotene and skin‐directed therapies, despite renal dysfunction and previous hypothyroidism. After 10 months of treatment, we observed neither new tumours nor disease recurrence, with complete response maintained at 24 months until now while continuing bexarotene. Our experience suggests that oral bexarotene is an effective treatment option, even for elderly patients with cATL.